Gender and Its Role in Family Education About Kids Friendly Entertainment - Jannah, Dejehave Al; Rahmadan, Yanuar (Jurnal Ilmiah Global Education, 2024)
The development of information technology is one of the advances of the times that cannot be denied, especially the COVID-19 pandemic has also encouraged the use of information technology among children as a new method of school learning. Supervision and education should be carried out to minimize exposure to negative content that is not age appropriate. This research comes with two main goals. First, find out whether supervision and education regarding children’s entertainment has been carried out, especially in Sunter Agung and Warakas sub-districts. Second, knowing which gender has the dominant role in carrying out that role. Considering that Indonesia's social and cultural conditions have long recognized the division of roles between men and women which originates from the idea of patriarchy. This research uses mixed research methods, qualitative and quantitative methods. The research results show that monitoring of gadget use has been carried out by involving a third side, in this case an age restriction algorithm to replace the role of parents. The gender that plays the dominant role in monitoring gadget use is women or mothers. This is based on two reasons. First, women are considered to spend more time interacting with children, especially those who work as housewives. Meanwhile, fathers don't interact much with their children because they work outside the home. Second, women are considered to have feminine qualities, such as patience and perseverance, which are considered better in educating children.